The Effectiveness of Memrise Application toward Students' Adjective Mastery - Pradana, Satria Adi; Marselina, Silvia Dwi; Yudha, Galang Tirta (English Education: Jurnal Tadris Bahasa Inggris, 2023)
This research was conducted because it was discovered that students had difficulty learning vocabulary, especially adjectives, and it was set against the background of several student problems. For instance, utilizing continuous paper-based learning to teach vocabulary resulted in boredom and could demotivate students. Dealing with that, one alternative solution was provided to the problem by implementing the memrise media to be tested in the learning process toteach adjectives. The research objective was to know the effectiveness of using memrise towards students' adjective mastery. Thus, this research used a quasi-experimental design and chose two classes by using cluster random sampling as the sample. The research instrument was tests, the results of which were analyzed using an independent sample t-test. The hypothesis testing results revealed that a significant value of 0.025 was obtained with a significance of α = 0.05. Thus, there was effectiveness in using memrise application toward students' adjective mastery. Furthermore, the N-Gain score for the control class was 0.46, while for the experimental class was 0.58. Therefore, it could be stated that the memrise can be used and is effective as learning mediafor adjectives mastery for seventh grade students of SMP N 3 Pringsewu